EVALUASI OUTPUT PROGRAM PEMBERANTASAN MALARIA (P2M) DI WILAYAH KERJA PUSKESMAS SEBA KECAMATAN SABU BARAT KABUPATEN KUPANG - Lado, Ie setiawan; Mado, Frans G.; Sirait, Rina Waty (Jurnal Pangan Gizi dan Kesehatan, 2010)
Malaria is one of the diseases that still becomes a threat, even often float the outbreaks (KLB) in the area that never found the malaria case before. It happened because the weakening of the care system early and the planning of eradication of malaria do not precisely and continual. To overcome this problem, needed the eradication program of malaria that doing by chronically and integrated. According to the Management Program of Eradication Malaria (P2M) Module and Program in Puskesmas Seba, there is some activity that acts as the effort to against malaria disease: 1)invention of the patient, 2) medication of patient, 3) spraying house and 4) distribution of mosquito’s net. The study is aimed to know the efficacy level of this program. Therefore, it’s necessary to evaluate the output of this program. The Type of this study is descriptive research with a qualitative approach. The population is the entire officer of health in Puskesmas Seba. The sample amount to 12 one who represents the overall population. Data analysed descriptively. Result of the research indicates that from 3 activity of invention patient (ACD, PCD, and Posmaldes), only 2 activity that is PCD and Posmaldes that doing.